2011
DOI: 10.1590/s1984-63982011000400006
|View full text |Cite
|
Sign up to set email alerts
|

Concept Maps powered by computer software: a strategy for enhancing reading comprehension in English for Specific Purposes

Abstract: This paper focuses on the procedures of an action-research (STRINGER, 2007) that was conducted with undergraduates enrolled in an ESP course at Faculdade de Letras (UFMG). The impelling drive was the creation of a means to solve an educational problem, namely, the enhancement of students' reading comprehension of texts in English for academic purposes. The problem-solving process involved the use of concept maps (NOVAK; CAÑAS, 2008) powered by the CMap Tools software (CAÑAS et al., 2004) to meet the educationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
(1 reference statement)
0
4
0
3
Order By: Relevance
“…They found that the computer-assisted concept mapping learning strategy had greater reading benefit for the low-level group than for the high-level group. Dias (2010), also, carried out a research on the effect of CM to enhance students' reading comprehension in English as L2. He found that creation of a visual representation of a text can enable students to follow how authors organize and bring together their arguments around a specific topic in the texts they write and as a result can be an effective reading strategy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the computer-assisted concept mapping learning strategy had greater reading benefit for the low-level group than for the high-level group. Dias (2010), also, carried out a research on the effect of CM to enhance students' reading comprehension in English as L2. He found that creation of a visual representation of a text can enable students to follow how authors organize and bring together their arguments around a specific topic in the texts they write and as a result can be an effective reading strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The result indicated that the concept mapping learning strategy was more effective for the low-level group than for the high-level group, in terms of their performance on reading comprehension (Liu, 2009). In the same vein, Dias (2010) examined the effect of strategy of concept map on the second language learners' reading comprehension. Results showed that the construction of meaning by the creation of concept maps could be an effective reading strategy in English as an L2 (Dias, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por outro lado, Frison (2016) revela que os docentes não estão preparados para aplicar atividades e estratégias baseadas na aprendizagem colaborativa. Para tanto, desafios de ordem técnica (DIAS, 2011;SIQUEIRA, 2012), pedagógica e pessoal (GON-ZÁLEZ; MARTÍN; ARRIBA, 2016; MORAIS; CABRITA, 2008) precisam ser superados, como a visão que o docente e o estudante têm sobre o processo de ensino e aprendizagem, que os faz privilegiar, muitas vezes, uma proposta de ensino magistral. O investimento na formação pedagógica, para que as estratégias desenvolvidas pelo docente possam ir além do trabalho em grupo, planejando atividades que motivem os estudantes a superar as inseguranças geradas quando da utilização de novas estratégias no processo de ensino e aprendizagem, é outro desafio a ser suplantado.…”
Section: Discussão Dos Resultadosunclassified
“…A categoria "tecnologias" (Figura 4) compreende 13 artigos e seus desafios relacionam-se ao uso de ferramentas de colaboração (BOTTENTUIT JUNIOR;COUTINHO, 2008;SANCHES;LOPES, 2008;ABEGG;BASTOS;MÜLLER, 2010;DIAS, 2011;SALOMÃO, 2015); ao manuseio do ambiente virtual (RUIZ-MORENO;PITTAMIGLIO;FURUSATO, 2008;PRADO et al, 2012;SILVA; ANDRIOLA, 2012; FERNÁNDEZ; RUIZ; GARCÍA, 2015; RABELLO, 2015; STRUCHINER; RAMOS; SERPA JUNIOR, 2016); à infraestrutura CABRITA, 2008); e a limites tecnológicos do ambiente virtual para a implementação de práticas colaborativas (SCHELLENS et al, 2007). Quanto à formação docente (oito artigos), também apresentada no Mapa Conceitual 4, destaca-se a importância de uma formação continuada qualificada para os docentes que decidam utilizar essa prática (RANGELS-S et al, 2012;SANTOS JUNIOR;SIQUEIRA, 2012;MARCONDES, 2013;FRISON, 2016), além de ser consideradas propostas tanto para a formação inicial quanto continuada de forma distinta, pois as necessidades são diferentes (GONZÁLEZ-WEIL et al, 2014).…”
Section: Desafios No Uso Da Prática De Aprendizagem Colaborativaunclassified